Epidemiological profile of acute bacterial meningitis in the state of Rio Grande do Norte, Brazil Perfil epidemiológico da meningite bacteriana aguda no estado do Rio Grande do Norte, Brasil - Wallace Andrino da Silva; Aline Macêdo Pinheiro; Leonam Gomes Coutinho; Luis Alberto Carneiro Marinho; Lucymara Fassarella Agnez Lima (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Acute bacterial meningitis (ABM) remains a public health problem in Brazil. To evaluate the epidemiology of ABM cases at Giselda Trigueiro Hospital, Rio Grande do Norte, a descriptive retrospective survey was conducted covering 2005 to 2008. METHODS: Clinical and laboratory data were collected from the epidemiology department of the hospital and analyzed. RESULTS: Out of 168 ABM cases, 24.4%, 10.7%, and 2.4% were, respectively, caused by Streptococcus pneumoniae, Neisseria meningitidis and Haemophilus influenza b, and 5.4% by other bacteria. The mean age was 22.48 ± 18.7 years old. CONCLUSIONS: Streptococcus pneumoniae was the main causative pathogen in the young urban population. INTRODUÇÃO: Meningite bacteriana aguda (MBA) permanece um problema de saúde pública no Brasil. Para avaliar a epidemiologia da MBA atendida no Hospital Giselda Trigueiro, Rio Grande do Norte, um estudo retrospectivo-descritivo foi realizado de 2005 a 2008. MÉTODOS: Dados clínicos e laboratoriais foram coletados do departamento de epidemiologia hospitalar e analisados. RESULTADOS: Dos 168 casos de MBA, 24,4%, 10,7% e 2,4% foram, respectivamente, causados por Streptococcus pneumoniae, Neisseria meningitidis e Haemophilus influenzae b e 5,4% por outras bactérias. A média da idade foi 22,48 ± 18,7 anos. CONCLUSÕES: Streptococcus pneumoniae foi o principal patógeno causador na população urbana jovem.